On Rates of Isopycnal Dispersion at the Submesoscale. Issue 12 (17th June 2021) - Rossby, T.; Omand, M.; Palter, J.; Hebert, D.
Abstract: Past studies of dispersion with float‐pairs have indicated that they may remain close together for much longer when they equilibrate on the same isopycnal, presumably due to the reduced influence of vertical shear. To examine this question more closely, we use a set of 13 and 15 float pair combinations that equilibrated within 0.1 °C (∼ σ θ = 0.01 kg m −3 ) of each other on two density surfaces in the main thermocline in a Lagrangian dispersion study. Their average rate of separation after launch was 0.0021 ± 0.0014 ms −1 (∼5.5 km after 30 days). Relative dispersion is accurately expressed by < D 2 > = 410 6 exp (t/10.8) m 2 from start to about 30 days. Relative diffusivity (K) versus separation dropped well below the classical 4/3rds power law settling out at about 2–3 m 2 s −1 for separations less than ∼6 km, far lower than results from other float studies, but in accord with dye dispersion estimates. Plain Language Summary: The study of dispersion and relative dispersion focuses on the rates spreading and mixing in the ocean. It has numerous practical applications such as predicting the impact of an oil spill, aiding search and rescue operations, or assessing the impact of coastal run‐off after severe storms. Dispersion within the ocean is also of great interest for it gives an important measure of eddy activity, lateral shear and mixing, processes that determine the observed distributions of water properties from heat and salt to CO2 and nutrients. Sub‐surface activity can be studied by tracking neutrally buoyant floats, drifting on constant density (isopycnal) surfaces, using acoustic navigation (RAFOS). But unless floats are on exactly the same surface, their relative motion may be affected by vertical shear, i.e., water at different depths moving at different speeds. In this study using float pairs that were deployed together and equilibrating on the same density surface we find that relative dispersion is very slow during the first few weeks as long as floats are closer than about 10 km. At greater separations being on exactly the same isopycnal surface matters less because their continued spread is increasingly dominated by the horizontal mesoscale eddy field. Key Points: Isopycnal floats deployed on the same isopycnal surface do not feel vertical shear and thus separate very slowly For larger separations, > 20 km, mesoscale eddy activity dominates, and the 4/3‐diffusivity law applies Relative dispersion is exponential with a 10.8 days time constant for the first 30 days